Early Years for Level 4 & 5 and the Foundation Degree - Veale, Francisca (2012)
The authoritative and comprehensive textbook to take you through your Level 4/5 vocational course or Foundation Degree.
Includes bibliographical references and index.
Keywords: Child care -- Great Britain; Early childhood education -- Great Britain; Society